Cell type-preferred expression of maize cab-m1: repression in bundle sheath cells and enhancement in mesophyll cells. - Bansal, K C (1993)
Different sets of genes for photosynthesis are expressed in mesophyll cells (MCs) and bundle sheath cells (BSCs)--the two adjacent but morphologically and functionally distinct types of photosynthetic cells in leaves of maize and other C4 plants. For example, light-harvesting chlorophyll a/b-binding proteins of photosystem II, which are encoded by a family of cab genes, are 3- to 4-fold more abundant in maize MCs than in BSCs. Each maize cab gene is different from the others in its relative expression in MCs vs. BSCs and in its degree of photoresponsiveness. The gene cab-m1 is positively photoregulated and is highly preferentially expressed in MCs. A 159-bp sequence in the 5' flanking region of this gene (-1026 to -868 relative to the translation start site) is required for MC-preferred expression of a reporter gene in greening maize leaves. Deletion as well as gain-of-function experiments have now shown that all of the sequence information required for MC-preferred expression resides within this mesophyll-specifying region and that cab-m1 is preferentially expressed in MCs because of the presence of two types of sequence elements: one is required for suppressing expression in BSCs and the other for promoting expression in MCs. One of the four cis-acting regions mapped within the mesophyll-specifying region resembles the AT-1 box of some plant gene negative regulatory elements. Various combinations of such MC-specific enhancing and BSC-specific repressing regions could make maize cab gene family members different from one another in their relative expression in MCs vs. BSCs.